Evaluation of Physicochemical Properties of Sandy-Textured Soils under Smallholder Agricultural Land Use Practices in Sarawak, East Malaysia - Soo, Ying Ho; Mohd Effendi, Bin Wasli; Mugunthan, A/L Perumal (Hindawi Publishing, 2019)
A study was conducted in the Sabal area, Sarawak, to evaluate the physicochemical properties of sandy-textured soils under smallholder agricultural land uses. Study sites were established under rubber, oil palm, and pepper land uses, in comparison to the adjacent secondary forests. *e sandy-textured soils underlain in all agricultural land uses are of Spodosols, based on USDA Soil Taxonomy. *e soil properties under secondary forests were strongly acidic with poor nutrient contents. Despite higher bulk density in oil palm farmlands, soil properties in rubber and oil palm land uses showed little variation to those in secondary forests. Conversely, soils under pepper land uses were less acidic with higher nutrient contents at the surface layer, especially P. In addition, soils in the pepper land uses were more compact due to human trampling effects from regular farm works at a localized area. Positive correlations were observed between soil total C and soil total N, soil exchangeable K, soil sum of bases, and soil effective CEC, suggesting that soil total C is the determinant of soil fertility under the agricultural land uses. Meanwhile, insufficient K input in oil palm land uses was observed from the partial nutrient balances estimation. In contrast, P and K did not remain in the soils under pepper land use, although the fertilizers application by the farmers was beyond the crop uptake and removal (harvesting). Because of the siliceous sandy nature (low clay contents) of Spodosols, they are poor in nutrient retention capacity. Hence, maintaining ample supply of organic C is crucial to sustain the productivity and fertility of sandy-textured soils, especially when the litterfall layers covering the E horizon were removed for oil palm and pepper cultivation.